2013
DOI: 10.4049/jimmunol.1300146
|View full text |Cite
|
Sign up to set email alerts
|

TPL-2–ERK1/2 Signaling Promotes Host Resistance against Intracellular Bacterial Infection by Negative Regulation of Type I IFN Production

Abstract: Tuberculosis, caused by Mycobacterium tuberculosis (Mtb), remains a leading cause of mortality and morbidity worldwide, causing approximately 1.4 million deaths per year. Key immune components for host protection during tuberculosis include the cytokines IL-12, IL-1 and TNF-α, as well as IFN-γ and CD4+ Th1 cells. However, immune factors determining whether individuals control infection or progress to active tuberculosis are incompletely understood. Excess amounts of type I interferon have been linked to exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
114
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 78 publications
6
114
1
Order By: Relevance
“…This report offers additional clarity on the role of Tpl2 in M. tuberculosis infection and covers new ground that has not previously been studied by other groups, such as McNab et al, who also demonstrated Tpl2-dependent induction of IL-10 and suppression of IL-12 in macrophages by M. tuberculosis (48). Among the multiple receptors that recognize M. tuberculosis, we demonstrate that TLR2 is responsible for activation of Tpl2 and ERK in M. tuberculosis-infected macrophages ( Fig.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This report offers additional clarity on the role of Tpl2 in M. tuberculosis infection and covers new ground that has not previously been studied by other groups, such as McNab et al, who also demonstrated Tpl2-dependent induction of IL-10 and suppression of IL-12 in macrophages by M. tuberculosis (48). Among the multiple receptors that recognize M. tuberculosis, we demonstrate that TLR2 is responsible for activation of Tpl2 and ERK in M. tuberculosis-infected macrophages ( Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Prior research has not connected Tpl2-ERK signaling in macrophages with regulation of T cell responses. Indeed, one of the major issues in understanding the role of Tpl2 is that in vitro, Tpl2 deletion facilitates a more proinflammatory macrophage response (this work and reference 48), but in vivo, Tpl2 is protective against M. tuberculosis (48). These in vivo results may be confounded by a combination of different roles for Tpl2 in different cell types, making the results of systemic Tpl2 knockout difficult to interpret mechanistically.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously demonstrated the critical role of Tpl2 in host defense against intracellular bacteria like Listeria monocytogenes and Mycobacterium tuberculosis (16,48). Defective ROS production in tpl2 Ϫ/Ϫ mice may contribute to decreased bacterial clearance, increased susceptibility to infection or altered redox-sensitive signaling (39,49).…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, Tpl2 Ϫ/Ϫ mice are more susceptible than wild-type mice to the Th1-inducing intracellular pathogens Toxoplasma gondii (22), Listeria monocytogenes (21), and Mycobacterium tuberculosis (23). M. tuberculosis is known to induce a mixed Th1/Th17 response (reviewed in reference 56), but whether Tpl2 impacted Th17 cell differentiation in this model was not investigated.…”
Section: Figmentioning
confidence: 99%
“…Tpl2 has been shown to promote Th1 cell differentiation and the production of IFN-␥ (22). Therefore, Tpl2 Ϫ/Ϫ mice experience greater susceptibility and infectious burden in response to the protozoan parasite Toxoplasma gondii (22) or the intracellular bacteria Listeria monocytogenes (21) and Mycobacterium tuberculosis (23) than wild-type mice. However, Tpl2 Ϫ/Ϫ mice are resistant to endotoxin-induced septic shock due to the reduced production of TNF (20).…”
mentioning
confidence: 99%